Wszczęcie postępowania sądowego w sprawach z zakresu ubezpieczeń społecznych - Jabłoński, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article discusses selected issues concerning the initiation of court proceedings in social security cases. The author begins his research by considering the legal approach of an appeal, which leads to the conclusion that it performs the role of the claim. The appeal does not necessarily have to meet the formal criteria of law suits due to the liberalisation of existing regulations.Furthermore, the term of appeal is also treated quite liberally by regulations. The appeal should be filed within one month of delivery of the decision, however, the case canal so be continued, when the failure to meet the deadline occurred due to reasons beyond control and was not excessive. Nonetheless, the fact that Polish Code of Civil Procedure does not directly regulate the problem of the response to an appeal raises objections. The question of which entities are authorized to file an appeal is acontroversial subject, but even more so is the question of whether an appeal could be filed by the interested party.
Keywords: wszczęcie postępowania sądowego; ubezpieczenie społeczne; roszczenia; odwołanie